Digital Activism Communications and Gender Equality Efforts: The #WeRaceAsOne Movement in Media Social by F1 Fans - Mumtaz, Faisa Amanta Binar; Pradita, Bramaningtyas Putri Dian; A'yun, Bintan Auliya Qurrota; Akalili, Awanis (Jurnal Komunikasi dan Bisnis, 2024)
The Formula 1 or F1 community is characterized by cases of gender discrimination and sexual harassment, such as the assumption that women do not deserve to like F1 and the Christian Horner harassment case that was not followed up. The purpose of this study is to analyze the form of digital activism used by F1 fans in addressing issues within the F1 community. The research method used is with a qualitative approach and focuses on content analysis. Content analysis of social media posts shows two main purposes for using the hashtag: (1) supporting victims of sexual harassment and (2) rejecting double standards against women in the F1 community. This research concludes that the #WeRaceAsOne hashtag initiated by F1, can be used by fans as a digital activism movement to solve the problems experienced by women in F1.With digital activism movements such as the use of the #WeRaceAsOne hashtag, it is expected to raise awareness, audience solidarity, support victims, ask F1 to be more assertive, and defend female fans who experience discrimination.